Usability Evaluation of The Android Operating System Using Use Questionnaire - Kilis, Billy M.H.; Mamonto, Julita; Legesan, Hizkia; Sagai, Zachary (International Journal of Information Technology and Education, 2022)
Usability aspects are used as a reference in measuring the level of usability of the Android operating system. Usability is important to use as an instrument to ensure an application can be useful according to user needs. This study aims to evaluate the usability of the Android operating system for users at universities. This study uses a use questionnaire that has aspects of effectiveness, efficiency, and satisfaction. Researchers used questionnaires with respondents at universities using the Android operating system for smartphone devices with 13 attributes of the questions asked. After obtaining the data, further analysis was carried out using the Likert scale method to obtain the percentage of usability values ​​on the Android operating system at the University. Usability measurement results show that all attributes have usability by the user, the average value is above 3, so it can be said that the android operating system used by the user already has a good usability aspect value. This study concludes that the android operating system with users at universities has a good adoption rate caused by easier use, ease to learn, and a good level of user satisfaction.